UnMarketing : everything has changed and nothing is different - Stratten, Scott; Stratten, Alison (Hoboken : Wiley, 2017)
"Stop marketing. Start UnMarketing. No one likes cold calls at dinnertime, junk mail overflowing your mailbox, and advertisements that interrupt your favorite shows. If this is "marketing," then the world would probably prefer whatever is the opposite of that. If you're ready to stop marketing and start engaging, then welcome to UnMarketing. The landscape of business-customer relationships is changing, and UnMarketing gives you innovative ways out of the old "Push and Pray" rut. Instead, draw the right customers to you through listening and engagement, enabling you to build trust and position yourself as their logical choice when they need you. This second edition includes new information on the rapidly changing marketing landscape, including details on targeted ads and search, Snapchat, brand engagement, and more"--
Machine generated contents note: Introduction Notes Everything Has Changed and Nothing is Different The Hierarchy of Buying A Word on Experts Trust Gap ROD. Return on Donuts Restaurant That Didn't Get It Cold Calling Aiming Your Company at the Bottom of the Barrel The Better Bottom of the Barrel Notes Pull and Stay Reasons Why Companies Don't Use Social Media Social Media (Social Currency as Well) Notes Twitter versus Facebook versus LinkedIn Conversational Social Visual Social Dark Social Social Media Platforming Notes UnPodcasting HARO Notes The Game Has Changed Immediacy and Relevancy Notes Publicized Customer Service Don't Bank on the Bold Seven Deadly Social Media Sins Greed Gluttony Sloth Envy Wrath Lust Pride Notes The Millennials Are Coming How Twitter Changed Scott's Business Notes Tassimo Notes Domino's--Word of Mouth Mouths Are Moving.
Revised edition of the author's UnMarketing, c2012.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Relationship marketing; Viral marketing; Electronic books